Categorization and Category Change. - Roy, Isabelle (Writer on linguistics) (Cambridge Scholars Publishing, 2013)
This collection of selected papers addresses theoretical and empirical issues related to lexical categories, categorization and category change. Any grammatical description makes use of parts-of-speech. The proper set of lexical categories and the definitions of their properties cross-linguistically has been a remnant issue in linguistics since the beginnings of grammatical description. Besides, the traditional classification of lexical classes with their morphological, syntactic and/or inter ...